2012
DOI: 10.1177/1089253211434966
|View full text |Cite
|
Sign up to set email alerts
|

Management of the Patient for Transcatheter Aortic Valve Implantation in the Perioperative Period

Abstract: Aortic stenosis is a prevalent valvular disease among aging patients, and surgical correction is the most definitive treatment. Yet many elderly patients are deemed to be "inoperable" or at excessive risk to undergo open surgical aortic valve replacement (AVR). Transcatheter aortic valve implantation (TAVI), either through a transfemoral or transapical approach, has become a potential option for these high-risk patients. Although TAVI technology will continue to be developed and perfected, most studies at this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 90 publications
0
20
0
Order By: Relevance
“…Further, a transfemoral transcatheter valve is more difficult to position than a valve inserted via a more direct approach. 38,39,41,42,46,48 Some studies have reported a higher incidence of neurologic events with the transfemoral route, which is probably because the sheath has to pass through the curved aortic arch, but others could not support these findings. 40,49,50 Introducing the valve through the left-ventricular apex is performed via a left anterior thoracotomy through the fifth or sixth intercostal space.…”
Section: Access Routesmentioning
confidence: 99%
See 4 more Smart Citations
“…Further, a transfemoral transcatheter valve is more difficult to position than a valve inserted via a more direct approach. 38,39,41,42,46,48 Some studies have reported a higher incidence of neurologic events with the transfemoral route, which is probably because the sheath has to pass through the curved aortic arch, but others could not support these findings. 40,49,50 Introducing the valve through the left-ventricular apex is performed via a left anterior thoracotomy through the fifth or sixth intercostal space.…”
Section: Access Routesmentioning
confidence: 99%
“…25 Of the two most commonly used valves, only the SAPIEN can be inserted transapically. 48,51 The transapical approach is feasible in the majority of patients, with exception of a few in whom a left-ventricular aneurysm or adhesions might prohibit this access route. 46 is a major advantage for the large group of patients with peripheral vascular disease.…”
Section: Access Routesmentioning
confidence: 99%
See 3 more Smart Citations